THE DEVELOPMENT OF CONTEXTUAL BIOLOGY HANDOUT FOR ANIMALIA TOPIC - Kusuma, Mobinta (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ Teaching material is one of essential material used by teacher as teaching tools. Handout is known as one of the teaching tools. It is important for teacher to develop their own teaching tools which support the teacher to achieve the learning indicators. Handout is one of the teaching materials that can be used by teachers or students in the learning process.There are many topics learned by students in senior high school. Animalia is one of the topics that can be learned by the student. It is a topic that has a wide scope. In senior high shcool, students should be able to learn the characteristic, example, the benefit of phylum for enviroment. Teachers need to develop teaching tool such as handout to figure out the wide concept of invertebrate by appliying contextual learning. Developing handout using Research and developnet design would help the teacher achieving purpose of the research. This research was aimed to determine whether the handout which had been developed was appropriate for use in senior high school. The research design applied in this research was a Research and Development (R&D). The research was done in some steps like data collection, planning, development of product, and evaluation stage. The subjects of this research were biology teachers and the students of senior high school. The experts’ judgment result of the integrated science handout was 83, teachers responses were 81.6%, students responses were 83.2% and students’ average score was 81.2 above the score of 75 as passing grade. It can be concluded that the developed handout meets the requirements as teaching materials.